A Multistate pH‐Triggered Nonlinear Optical Switch. Issue 11 (23rd May 2014) - Castet, Frédéric; Champagne, Benoît; Pina, Fernando; Rodriguez, Vincent
Abstract By using hyper‐Rayleigh scattering experiments and quantum‐chemical calculations, we demonstrate that nonlinear optics can be used to probe unequivocally, within a non‐destructive process, the multiple electronic states that are activated upon pH‐ and light‐triggered transformations of the 4′‐hydroxyflavylium ion. These results open new perspectives in the design of molecular‐scale high‐density optical memory.